LC/MS analysis and deep sequencing reveal the accurate RNA composition in the HIV-1 virion - Šimonová, Anna; Svojanovská, Barbora; Trylčová, Jana; Hubálek, Martin; Moravčík, Ondřej; Zavřel, Martin; Pávová, Marcela; Hodek, Jan; Weber, Jan; Cvačka, Josef; Pačes, Jan; Cahová, Hana (Scientific reports, 2019)
The mechanism of action of various viruses has been the primary focus of many studies. Yet, the data on RNA modifications in any type of virus are scarce. Methods for the sensitive analysis of RNA modifications have been developed only recently and they have not been applied to viruses. In particular, the RNA composition of HIV-1 virions has never been determined with sufficiently exact methods. Here, we reveal that the RNA of HIV-1 virions contains surprisingly high amount of the 1-methyladenosine. We are the first to use a liquid chromatography-mass spectrometry analysis (LC/MS) of virion RNA, which we combined with m1A profiling and deep sequencing. We found that m1A was present in the tRNA, but not in the genomic HIV-1 RNA and the abundant 7SL RNA. We were able to calculate that an HIV-1 virion contains per 2 copies of genomic RNA and 14 copies of 7SL RNA also 770 copies of tRNA, which is approximately 10 times more than thus far expected. These new insights into the composition of the HIV-1 virion can help in future studies to identify the role of nonprimer tRNAs in retroviruses. Moreover, we present a promising new tool for studying the compositions of virions.
Keywords: RNA, Small Cytoplasmic; RNA malá cytoplazmatická; RNA virová; Adenosine; Chromatography, Liquid; Humans; sekvence nukleotidů; RNA, Transfer; genom virový; virion; signál-rozpoznávající částice; lidé; RNA transferová; chromatografie kapalinová; Base Sequence; Genome, Viral; sestavení viru; Virion; vysoce účinné nukleotidové sekvenování; nádorové buněčné linie; RNA, Viral; High-Throughput Nucleotide Sequencing; Signal Recognition Particle; Cell Line, Tumor; Virus Assembly; HIV-1; hmotnostní spektrometrie; adenosin; Mass Spectrometry